2015
DOI: 10.1248/bpb.b14-00712
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and Beneficial Metabolic Activities of Resveratrol in Type II Gaucher Disease

Abstract: Gaucher disease (GD) is one of the most common lysosomal storage disorders and is caused by an inherited deficiency in glucocerebrosidase. Resveratrol is a phytoalexin that has many beneficial activities, including anti-oxidant, anti-apoptotic, and neuroprotective effects. The aim of this study was to determine if resveratrol has a therapeutic effect on primary fibroblast cells derived from a patient with type II GD. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays were performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Consistent with data indicating that cells from human patients suffering from GD and FD are more susceptible to apoptosis (De Francesco, Mucci, Ceci, Fossati, & Rozenfeld, ; Wei et al, ; Yoo & Kim, ), we demonstrated that GBA and GLA deficiency determined a significantly increased percentage of apoptotic cells in both stem cell cultures (Fig. A).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with data indicating that cells from human patients suffering from GD and FD are more susceptible to apoptosis (De Francesco, Mucci, Ceci, Fossati, & Rozenfeld, ; Wei et al, ; Yoo & Kim, ), we demonstrated that GBA and GLA deficiency determined a significantly increased percentage of apoptotic cells in both stem cell cultures (Fig. A).…”
Section: Discussionsupporting
confidence: 91%
“…Even when biosynthesized in both its cis and trans configurations, a wide consensus considers the trans structure as more biologically active, besides being the most stable isomer (Pantusa et al 2014 ). This pharmacological activity of resveratrol has been studied in cardiovascular systems, inflammation, carcinogenesis, aging, diabetes, neurological dysfunction, and lysosomal storage diseases (Galiniak et al 2019 , Aggarwal et al 2004 ; Rintz et al 2020 ; Yoo and Kim 2015 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects of resveratrol have also been reported for Gaucher disease, a lysosomal storage disorder caused by deficiency of glucocerebrosidase. In Gaucher disease patientderived fibroblasts, treatment with resveratrol caused a reduction in the storage of glucosylceramides [65] and enhanced the viability of these cells [66]. These outcomes were correlated with decreased levels of the apoptotic factors AIF, Bax, and cleaved caspase-3.…”
Section: Discussionmentioning
confidence: 97%
“…These outcomes were correlated with decreased levels of the apoptotic factors AIF, Bax, and cleaved caspase-3. On the other hand, the concentrations of ACAT1, E3BP, and CS were increased in resveratrol-treated cells [65,66]. Interestingly, the possible involvement of autophagy modulation induced by resveratrol has been suggested in studies on mutants in the Drosophila GBA1 gene (encoding glucocerebrosidase) [67].…”
Section: Discussionmentioning
confidence: 99%